High-efficiency flame-retardant heat-insulating expandable polystyrene and graphite composite material and preparation method thereof

By using raw materials such as styrene and graphite, high-efficiency flame retardant, heat-insulating and radiating polystyrene and graphite composite materials were prepared, which solved the problems of flammable and poor mechanical properties of existing EPS insulation materials, and achieved good flame retardant, heat-insulating and mechanical properties.

CN112080083BActive Publication Date: 2025-03-07TIANJIN JIATAI WEIYE CHEM IND CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202010958241.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-09-14
Publication Date
2025-03-07
Estimated Expiration
2040-09-14

AI Technical Summary

Technical Problem

The existing EPS insulation materials have problems such as flammable, low thermal deformation temperature, decomposition and toxic gases, and weak mechanical properties. The large amount of flame retardant will damage the stability and mechanical properties of the material.

Method used

Using raw materials such as styrene, graphite, inorganic suspension agent, organic suspension agent and other raw materials, through specific ratios and process steps, an efficient flame retardant, heat-insulating and inducible polystyrene and graphite composite material is prepared.

Benefits of technology

It has achieved good flame retardant and fire resistance, excellent thermal insulation and improved mechanical properties of the material. It has fewer powdered particles and combustion performance reaches the B-level standard.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002679431420000191
    Figure BDA0002679431420000191
  • Figure BDA0002679431420000201
    Figure BDA0002679431420000201
Patent Text Reader

Abstract

The invention discloses a high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material. The composite material comprises the following raw materials in parts by weight: 70-100 parts of styrene, 150-240 parts of desalted water, 5-7.6 parts of foaming agent, 0.2-0.7 parts of initiator, 0.1-0.5 parts of nucleating agent, 0.5-4.5 parts of flame retardant, 0.01-0.08 parts of inorganic sodium salt, 0.01-3 parts of graphite, 0.05-0.2 parts of inorganic suspending agent, 0.0001-0.0005 parts of organic suspending agent, 0.001-0.005 parts of dispersant, 0.01-2 parts of inorganic filler, 0.001-0.005 parts of pH regulator and 0.003-0.005 parts of bead distribution regulator. The product obtained by the present invention has fewer powdery particles, and its combustion performance fully meets the requirements of Class B in the "Classification of Combustion Performance of Building Materials and Products", and has good flame retardant and fireproof performance and thermal insulation performance; and while ensuring flame retardant and thermal insulation performance, it has excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of composite materials, and in particular to a high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material and a preparation method thereof. Background Art

[0002] Building energy conservation is one of the important ways to reduce environmental pollution and solve the energy crisis. As a new concept of energy-saving buildings, "passive houses" are an important opportunity and platform for my country to promote building energy conservation. The lower energy consumption standard of "passive houses" is achieved through high thermal insulation and sound insulation, strong sealing of building exterior walls and renewable energy. Expandable polystyrene (EPS) foam insulation board is applied to the field of building energy-saving materials due to its advantages of thermal insulation, unique buffering and seismic resistance, anti-aging and waterproof properties, as well as light weight and low price.

[0003] However, EPS insulation materials often contain olefin substances, and the heat deformation temperature of polystyrene is relatively low (70-98°C). After ignition, it is easy to burn quickly and decompose to produce a large amount of toxic gases. At the same time, the current EPS insulation materials also have problems such as weak mechanical properties such as tensile strength. At present, EPS insulation materials used in the domestic construction industry often add a large amount of flame retardants to improve the flame retardant properties, but there are disadvantages such as excessive addition of flame retardants destroying the stability and mechanical properties of the material. Therefore, it is urgent to develop an expandable polystyrene and graphite composite material with excellent mechanical properties and high efficiency flame retardancy and heat insulation. Summary of the invention

[0004] In order to solve the above technical problems, the first aspect of the present invention provides a high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, comprising the following raw materials in parts by weight: 70 to 100 parts of styrene, 150 to 240 parts of desalted water, 5 to 7.6 parts of foaming agent, 0.2 to 0.7 parts of initiator, 0.1 to 0.5 parts of nucleating agent, 0.5 to 4.5 parts of flame retardant, 0.01 to 0.08 parts of inorganic sodium salt, 0.01 to 3 parts of graphite, 0.05 to 0.2 parts of inorganic suspending agent, 0.0001 to 0.0005 parts of organic suspending agent, 0.001 to 0.005 parts of dispersant, 0.01 to 2 parts of inorganic additive, 0.001 to 0.005 parts of pH regulator, and 0.003 to 0.005 parts of bead distribution regulator.

[0005] As a preferred technical solution, the initiator is selected from a combination of one or more of benzoyl peroxide, tert-butyl perbenzoate, tert-amyl peroxide-2-ethylhexyl carbonate, diisopropylbenzene peroxide, di-tert-butyl cyclohexyl peroxydicarbonate, and azobisisobutyronitrile.

[0006] As a preferred technical solution, the particle size of the graphite is 1 to 50 μm.

[0007] As a preferred technical solution, the graphite is surface-treated graphite.

[0008] As a preferred technical solution, the organic suspending agent is selected from one or more combinations of hydroxyethyl cellulose, gelatin, starch, methyl cellulose, and hydroxymethyl cellulose.

[0009] As a preferred technical solution, the inorganic suspending agent is selected from a combination of one or more of active calcium phosphate, magnesium carbonate, magnesium phosphate and barium sulfate.

[0010] As a preferred technical solution, the weight ratio of the graphite, the organic suspending agent and the inorganic suspending agent is 1: (0.0001-0.02): (0.06-10).

[0011] As a preferred technical solution, the dispersant is polyvinyl alcohol and / or polypropylene alcohol.

[0012] As a preferred technical solution, the raw material also includes an additive; the additive is selected from a combination of one or more of a lubricant, an antistatic agent, a reducing agent, a plasticizer, a coating agent, a synergistic flame retardant, and a plastic stabilizer.

[0013] The second aspect of the present invention provides a method for preparing the high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, comprising the following steps:

[0014] Step 1: maintaining a rotation speed of 50-70 r / min, adding inorganic suspending agent, organic suspending agent, inorganic sodium salt, graphite, inorganic additives and stirring for 20-40 minutes, then continuing to add styrene, nucleating agent, flame retardant, pH adjuster, initiator and stirring for 20-40 minutes, adding desalted water and dispersant into the reactor, stirring at 90°C for 20-40 minutes and then cooling to room temperature to obtain an aqueous suspension;

[0015] Step 2: The aqueous suspension obtained in step 1 is heated to 85-90° C., kept warm for 0.5-1.5 hours, and then a bead distribution regulator is added. After being kept warm for 5-6 hours, a mixed suspension material is obtained;

[0016] Step 3: adding a stabilizer to the mixed suspension material obtained in step 2 until the mixed suspension material is stable, filling the reactor with nitrogen, adding a foaming agent, continuing to heat to 115-130° C., keeping the temperature at 0.8-0.9 MPa for 2-2.5 hours, and cooling to 30-40° C. to obtain a bead material;

[0017] Step 4: Dehydrate, dry and package the bead material obtained in step 3 to obtain a highly efficient flame retardant and heat insulating expandable polystyrene and graphite composite material.

[0018] Beneficial effects: The present invention uses styrene, graphite, inorganic suspending agent, organic suspending agent and other additives to prepare a highly efficient flame retardant and heat insulating expandable polystyrene and graphite composite material with excellent performance. The product obtained by the present invention has fewer powder particles, and after being made into a polystyrene (EPS) board, the combustion performance fully meets the requirements of Class B in the "Classification of Combustion Performance of Building Materials and Products", and has good flame retardant and fireproof performance and thermal insulation performance; and while ensuring flame retardant and heat insulation performance, it has excellent mechanical properties. DETAILED DESCRIPTION

[0019] The following is a further clear and complete description of the technical features in the technical solution provided by the present invention in conjunction with specific implementation methods, which is not intended to limit the scope of protection thereof.

[0020] The words "preferred", "more preferred" and the like in the present invention refer to embodiments of the present invention that can provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.

[0021] In order to solve the above technical problems, the first aspect of the present invention provides a high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, comprising the following raw materials in parts by weight: 70 to 100 parts of styrene, 150 to 240 parts of desalted water, 5 to 7.6 parts of foaming agent, 0.2 to 0.7 parts of initiator, 0.1 to 0.5 parts of nucleating agent, 0.5 to 4.5 parts of flame retardant, 0.01 to 0.08 parts of inorganic sodium salt, 0.01 to 3 parts of graphite, 0.05 to 0.2 parts of inorganic suspending agent, 0.0001 to 0.0005 parts of organic suspending agent, 0.001 to 0.005 parts of dispersant, 0.01 to 2 parts of inorganic additive, 0.001 to 0.005 parts of pH regulator, and 0.003 to 0.005 parts of bead distribution regulator.

[0022] In a preferred embodiment, the high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material comprises the following raw materials in parts by weight: 95 parts of styrene, 160 parts of desalted water, 6.3 parts of foaming agent, 0.3 parts of initiator, 0.2 parts of nucleating agent, 2.0 parts of flame retardant, 0.03 parts of inorganic sodium salt, 0.01 parts of graphite, 0.1 parts of inorganic suspending agent, 0.0002 parts of organic suspending agent, 0.002 parts of dispersant, 0.05 parts of inorganic additive, 0.002 parts of pH regulator, and 0.004 parts of bead distribution regulator.

[0023] <Styrene>

[0024] Styrene, CAS No. 100-42-5, is an organic compound formed by replacing one hydrogen atom of ethylene with benzene. It is an important monomer for synthetic resins, ion exchange resins and synthetic rubber in industry.

[0025] The present invention has no particular limitation on the styrene, and various styrenes well known to those skilled in the art may be used, for example, styrenes may be purchased from Qilu Petrochemical.

[0026] <Desalted water>

[0027] Desalted water is water whose easily removable strong electrolytes are removed or reduced to a certain level.

[0028] In a preferred embodiment, the conductivity of the desalted water is lower than 3 μs / cm.

[0029] In a more preferred embodiment, the conductivity of the desalted water is 1 μs / cm.

[0030] The μs / cm, i.e., microSiemens per centimeter, is a unit of conductivity and is a parameter used to describe the ease of charge flow in a substance. The present invention has no particular restrictions on the method for measuring the conductivity, and various conductivity test methods well known to those skilled in the art can be used, such as using a conductivity tester. The present invention has no particular restrictions on the method for controlling the conductivity of the desalted water, and various conductivity control methods well known to those skilled in the art can be used, such as reverse osmosis / ion exchange resin treatment.

[0031] <Foaming agent>

[0032] In a preferred embodiment, the blowing agent is isopentane and / or n-pentane.

[0033] In a more preferred embodiment, the blowing agent is a mixture of isopentane and n-pentane.

[0034] In a preferred embodiment, the weight ratio of isopentane to n-pentane is 1:(2-3).

[0035] In a more preferred embodiment, the weight ratio of isopentane to n-pentane is 1:2.3.

[0036] In a preferred embodiment, the raw material further includes an auxiliary agent.

[0037] <Initiator>

[0038] In a preferred embodiment, the initiator is selected from benzoyl peroxide (CAS No. 94-36-0), tert-butyl perbenzoate (CAS No. 614-45-9), tert-amyl peroxide-2-ethylhexyl carbonate (CAS No. 70833-40-8), diisopropylbenzene peroxide (CAS No. 80-43-3), di-tert-butyl cyclohexyl peroxydicarbonate (CAS No. 15520-11-3), and azobisisobutyronitrile (CAS No. 78-67-1). One or more combinations thereof.

[0039] In a more preferred embodiment, the initiator is selected from a combination of one or more of benzoyl peroxide, tert-butyl perbenzoate, tert-amyl peroxide-2-ethylhexyl carbonate, and dicumyl peroxide.

[0040] In a further preferred embodiment, the initiator is a mixture of benzoyl peroxide, tert-butyl perbenzoate, tert-amyl peroxide-2-ethylhexyl carbonate, and dicumyl peroxide.

[0041] In a preferred embodiment, the weight ratio of the benzoyl peroxide, tert-butyl perbenzoate, tert-amyl peroxide-2-ethylhexyl carbonate, and dicumyl peroxide is (5-7):(1-2):(1-2):(2.5-4).

[0042] In a more preferred embodiment, the weight ratio of benzoyl peroxide, tert-butyl perbenzoate, tert-amyl peroxide-2-ethylhexyl carbonate, and dicumyl peroxide is 6:1.5:1.5:3.25.

[0043] <Nucleating agent>

[0044] Nucleating agent, namely polyethylene wax, CAS No. 9002-88-4, is an additive used in polyolefin processing.

[0045] In a preferred embodiment, the molecular weight of the nucleating agent is 500-5000.

[0046] In a more preferred embodiment, the molecular weight of the nucleating agent is 2000-2500.

[0047] In a further preferred embodiment, the molecular weight of the nucleating agent is 2250.

[0048] The molecular weight, i.e., relative molecular mass, is not particularly limited in the present invention to its testing method, and various molecular weight testing methods well known to those skilled in the art can be used, such as gel permeation chromatography. The polyethylene wax can be purchased commercially, for example, from Qingdao Haihao Chemical Co., Ltd., model H100P, with a molecular weight of 2000-2500 (average molecular weight of 2250).

[0049] <Flame retardant>

[0050] In a preferred embodiment, the flame retardant is selected from tris(2-chloropropyl) phosphate (flame retardant TCPP), tris(1,3-dichloropropyl) phosphate (flame retardant TDCPP), hexabromocyclododecane (flame retardant HBCD), melamine cyanurate (flame retardant MCA), tris(2,3-dibromopropyl) isocyanurate (flame retardant TBC), melamine polyphosphate (flame retardant MPP), decabromodiphenyl ethane, ammonium polyphosphate, decabromodiphenyl ether, and zinc borate. One or more combinations thereof.

[0051] <Inorganic sodium salt>

[0052] In a preferred embodiment, the inorganic sodium salt is selected from a combination of one or more of trisodium phosphate, tetrasodium phosphate, sodium sulfate and sodium dichromate.

[0053] In a more preferred embodiment, the inorganic sodium salt is tetrasodium phosphate.

[0054] The tetrasodium phosphate is also called sodium pyrophosphate and has a CAS number of 7722-88-5.

[0055] <Graphite>

[0056] In a preferred embodiment, the particle size of the graphite is 1 to 50 μm.

[0057] In a more preferred embodiment, the particle size of the graphite is 20 to 30 μm.

[0058] In a further preferred embodiment, the particle size of the graphite is 25 μm.

[0059] The graphite is commercially available, for example, from Qingdao Shuofeng Graphite Products Co., Ltd., with a particle size of 25 μm.

[0060] In a preferred embodiment, the graphite is surface-treated graphite.

[0061] In a preferred embodiment, the method for preparing the surface-treated graphite comprises the following steps: adding 0.65 to 0.93 parts by weight of graphite and 0.65 to 0.9 parts by weight of a surfactant to 50 to 60 parts by weight of pure water, heating to 65 to 75° C., stirring for 10 to 14 hours, washing with water, and drying.

[0062] In a more preferred embodiment, the method for preparing the surface-treated graphite comprises the following steps: adding 0.79 parts by weight of graphite and 0.77 parts by weight of a surfactant to 55 parts by weight of pure water, heating to 70° C., stirring for 12 hours, washing with water, and drying.

[0063] In a preferred embodiment, the surfactant is a sulfonate surfactant.

[0064] In a more preferred embodiment, the sulfonate surfactant is selected from one or more combinations of sodium dodecylbenzenesulfonate (CAS No. 25155-30-0), sodium lignin sulfonate (CAS No. 8061-51-6), sodium dibutylnaphthalenesulfonate (CAS No. 25417-20-3), and sodium diisopropylnaphthalenesulfonate (CAS No. 1322-93-6).

[0065] In a further preferred embodiment, the sulfonate surfactant is sodium lignin sulfonate (CAS No. 8061-51-6).

[0066] The sodium lignin sulfonate is commercially available, for example, from Tianjin Shengfujiang Technology Co., Ltd., model number MN.

[0067] The inventors found in the long-term research and development process that the graphite treated with sulfonate surfactants can not only improve the dispersion stability of graphite to a certain extent, but also improve the flame retardant properties and thermal conductivity of the material. This is because the cyclic hydrophobic structure of the sulfonate surfactant sodium lignin sulfonate can cover the graphite layer by layer, and its molecular long chain is partially interspersed in the coating structure, increasing the range of hydrophobic groups and improving the stability of the styrene water-in-oil system; and the atoms in the same plane in the unique lamellar structure of graphite are covalently bonded, which can reflect infrared rays well under the condition of good dispersion, so that the thermal conductivity of EPS foam material is further reduced; and the graphite dispersed in the system can also absorb the α hydrogen atoms activated on the main chain skeleton of polystyrene when heated, and cooperate with the flame retardant to form a continuous and dense carbon layer on the surface of the material, which can block the external heat and isolate the material from the contact with the external air, and the addition of graphite improves the carbonization of the material, thereby improving the flame retardant properties of the material while also reducing the generation of combustible volatile products. However, due to the weak van der Waals force between adjacent layers in graphite and the long molecular chain of sodium lignin sulfonate affecting the intermolecular force of polymer to a certain extent, the mechanical properties of the resulting material cannot meet the application standards of expandable polystyrene.

[0068] <Inorganic suspending agent>

[0069] In a preferred embodiment, the inorganic suspending agent is selected from a combination of one or more of active calcium phosphate, magnesium carbonate, magnesium phosphate and barium sulfate.

[0070] In a more preferred embodiment, the inorganic suspending agent is activated calcium phosphate.

[0071] In a preferred embodiment, the active calcium phosphate is surface-treated active calcium phosphate.

[0072] In a preferred embodiment, the method for preparing the surface-treated active calcium phosphate comprises the following steps: adding active calcium phosphate, dispersant and water into a container in a weight ratio of 1: (0.05-0.12): (50-60), stirring at 50-70° C. until the active calcium phosphate is uniformly mixed, and drying to obtain the surface-treated active calcium phosphate.

[0073] In a more preferred embodiment, the method for preparing the surface-treated active calcium phosphate comprises the following steps: adding active calcium phosphate, a polyol-type surfactant, and water into a container in a weight ratio of 1:0.08:55, stirring at 60° C. until the active calcium phosphate is uniformly mixed, and drying to obtain the surface-treated active calcium phosphate.

[0074] The active calcium phosphate, i.e., the suspending agent TCP, has a molecular formula of Ca 2(PO4) 6 (OH) 2 , is a water-insoluble inorganic fine powder.

[0075] In a preferred embodiment, the polyol surfactant is selected from a combination of one or more of pentaerythritol fatty acid esters, lauric acid monoglyceride (CAS No. 142-18-7), glycerol fatty acid esters (CAS No. 542-44-9), and polyglycerol-6 stearate (CAS No. 95461-65-7).

[0076] In a more preferred embodiment, the polyol surfactant is lauric acid monoglyceride.

[0077] The inventor unexpectedly discovered during the research and development process that when the inorganic suspending agent used is an active calcium phosphate treated with a polyol-type surfactant, not only does it not reduce the suspension rate of the system, but the mechanical properties and flame retardant properties of the obtained material are significantly improved, and the thermal conductivity of the obtained material can be reduced. The inventor speculates that the possible reason is that, on the one hand, the active calcium phosphate treated with the polyol-type surfactant monolauric acid glycerol, the long-chain alkyl chain on the molecular surface, can be interspersed in the graphite coating structure, and staggered with the long chain of the sodium lignin sulfonate molecule, while improving the stability of the system, it also promotes the adsorption of the sodium lignin sulfonate molecule on its particle surface, filling the gaps in the system network structure, and significantly improving the mechanical properties of the obtained material; on the other hand, the treated active calcium phosphate can also cooperate with graphite to form an insulating aggregation structure, thereby reducing the thermal conductivity of the obtained material, and the active groups on its larger specific surface area also provide a certain amount of activated α hydrogen atom binding points, further promoting the formation of a continuous and dense carbon layer on the material surface, and improving the flame retardant properties of the obtained material. But at the same time, the specific active calcium phosphate and graphite after surface treatment cause too much mechanical isolation of styrene when forming droplets, which easily generates too many powdery particles. This is also a major problem that the inventors have to solve.

[0078] <Organic suspending agent>

[0079] In a preferred embodiment, the organic suspending agent is selected from one or more combinations of hydroxyethyl cellulose, gelatin, starch, methyl cellulose, and hydroxymethyl cellulose.

[0080] In a more preferred embodiment, the organic suspending agent is hydroxyethyl cellulose (CAS No. 9004-62-0).

[0081] In a preferred embodiment, the weight ratio of the graphite, the organic suspending agent, and the inorganic suspending agent is 1: (0.0001-0.02): (0.06-10).

[0082] In a more preferred embodiment, the weight ratio of the graphite, the organic suspending agent, and the inorganic suspending agent is 1:0.02:10.

[0083] <Dispersant>

[0084] In a preferred embodiment, the dispersant is polyvinyl alcohol and / or polypropylene alcohol.

[0085] In a more preferred embodiment, the dispersant is polyvinyl alcohol.

[0086] In a preferred embodiment, the degree of alcoholysis of the polyvinyl alcohol is 87-89 mole%.

[0087] In a more preferred embodiment, the degree of alcoholysis of the polyvinyl alcohol is 88 mole%.

[0088] The polyvinyl alcohol (PVA), with the CAS number 9002-89-5, is PVA-217 of Kuraray Japan, and the degree of alcoholysis is 87-89 mole% (the average value is 88 mole%). The degree of alcoholysis refers to the molar percentage of hydroxyl groups in the product obtained after alcoholysis in the original groups. The present invention does not have any special restrictions on its testing method, and various testing methods well-known to those skilled in the art can be used, such as the NaOH titration method.

[0089] The inventors unexpectedly found in further exploration and practice that when the weight ratio of the graphite, the organic suspending agent, and the inorganic suspending agent used is 1:(0.0001-0.02):(0.06-10), and the degree of alcoholysis of the dispersant polyvinyl alcohol is 87-89 mole%, the mechanical properties of the obtained material are further improved, and the content of the bead material is also greatly increased. The possible reason is that when using the dispersant polyvinyl alcohol with a degree of alcoholysis of 87-89 mole%, the organic suspending agent hydroxyethyl cellulose can be partially dissolved in the water phase and wrap on the surface of the treated graphite and the inorganic suspending agent active calcium phosphate, promoting the re-bonding of the too-small droplets into normal-sized droplets; for the relatively large monomer droplets, due to the limitation of its coating ability, it can only be adsorbed on the surface of the droplets and form a liquid film protection layer between a small part of the lignosulfonate molecular chains and the monolaurin molecular chains on the surface of the droplets, thereby greatly increasing the content of the bead material in the obtained material.

[0090] <Inorganic filler>

[0091] The present invention does not have any special restrictions on the inorganic filler, and various inorganic fillers can be selected according to the situation, such as a combination of one or more of carbon black, silica, and mica powder.

[0092] <pH regulator>

[0093] The present invention has no particular limitation on the pH adjuster, and various pH adjusters may be selected as appropriate, for example, at least one of sodium bicarbonate, ammonium carbonate, sodium hydroxide, ammonium hydroxide, dimethylaminoethanol and calcium carbonate may be included.

[0094] <Bead Distribution Regulator>

[0095] Bead distribution regulator is a reagent used in the field of expandable polystyrene to adjust and control the suspended particles to be between 0.5 and 5 mm.

[0096] The present invention has no particular limitation on the bead distribution regulator, and various bead distribution regulators well known to those skilled in the art may be used, such as sodium bisulfite.

[0097] <Auxiliary Agents>

[0098] In a more preferred embodiment, the raw material further comprises 0.41 to 0.65 parts by weight of an auxiliary agent.

[0099] In a further preferred embodiment, the raw material further comprises 0.53 parts by weight of an auxiliary agent.

[0100] In a preferred embodiment, the auxiliary agent is selected from a combination of one or more of a lubricant, an antistatic agent, a reducing agent, a plasticizer, a coating agent, a synergistic flame retardant, and a plastic stabilizer.

[0101] In a more preferred embodiment, the auxiliary agent is a lubricant and an antistatic agent.

[0102] In a further preferred embodiment, the weight ratio of the lubricant to the antistatic agent is (6-25):1.

[0103] In a further preferred embodiment, the weight ratio of the lubricant to the antistatic agent is 14:1.

[0104] The present invention has no particular limitation on the antistatic agent, and various antistatic agents known in the art may be used, such as polyethylene glycol PEG-400.

[0105] In a preferred embodiment, the lubricant is zinc stearate and monoglyceride (CAS No. 123-94-4).

[0106] In a more preferred embodiment, the weight ratio of zinc stearate to monoglyceride is (1-2.5):1.

[0107] In a further preferred embodiment, the weight ratio of zinc stearate to monoglyceride is 1.5:1.

[0108] The second aspect of the present invention provides a method for preparing the high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, comprising the following steps:

[0109] Step 1: maintaining a rotation speed of 50-70 r / min, adding inorganic suspending agent, organic suspending agent, inorganic sodium salt, graphite, inorganic additives and stirring for 20-40 minutes, then continuing to add styrene, nucleating agent, flame retardant, pH adjuster, initiator and stirring for 20-40 minutes, adding desalted water and dispersant into the reactor, stirring at 90°C for 20-40 minutes and then cooling to room temperature to obtain an aqueous suspension;

[0110] Step 2: The aqueous suspension obtained in step 1 is heated to 85-90° C., kept warm for 0.5-1.5 hours, and then a bead distribution regulator is added. After being kept warm for 5-6 hours, a mixed suspension material is obtained;

[0111] Step 3: adding a stabilizer to the mixed suspension material obtained in step 2 until the mixed suspension material is stable, filling the reactor with nitrogen, adding a foaming agent, continuing to heat to 115-130° C., keeping the temperature at 0.8-0.9 MPa for 2-2.5 hours, and cooling to 30-40° C. to obtain a bead material;

[0112] Step 4: Dehydrate, dry and package the bead material obtained in step 3 to obtain a highly efficient flame retardant and heat insulating expandable polystyrene and graphite composite material.

[0113] In a preferred embodiment, the method for preparing the high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material comprises the following steps:

[0114] Step 1: maintaining a rotation speed of 60 r / min, adding inorganic suspending agent, organic suspending agent, inorganic sodium salt, graphite, inorganic additives and stirring for 30 minutes, then adding styrene, nucleating agent, flame retardant, pH adjuster, initiator and stirring for 30 minutes, adding desalted water and dispersant into the reactor, stirring at 90°C for 30 minutes and then cooling to room temperature to obtain an aqueous suspension;

[0115] Step 2: The aqueous suspension obtained in step 1 is heated to 90° C., kept warm for 1 hour, and then a bead distribution regulator is added. After keeping warm for 5.3 hours, a mixed suspension material is obtained;

[0116] Step 3: Add a stabilizer to the mixed suspension material obtained in step 2 until the mixed suspension material is stable, fill the reactor with nitrogen, add a foaming agent, continue to heat to 122.5° C., keep warm at a pressure of 0.85 MPa for 2.2 hours, and then cool to 35° C. to obtain a bead material;

[0117] Step 4: Dehydrate, dry and package the bead material obtained in step 3 to obtain a highly efficient flame retardant and heat insulating expandable polystyrene and graphite composite material.

[0118] In another preferred embodiment, the method for preparing the high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material comprises the following steps:

[0119] Step 1: maintaining a rotation speed of 60 r / min, adding inorganic suspending agent, organic suspending agent, inorganic sodium salt, graphite, inorganic additives and stirring for 30 minutes, then adding styrene, nucleating agent, flame retardant, pH adjuster, initiator and stirring for 30 minutes, adding desalted water and dispersant into the reactor, stirring at 90°C for 30 minutes and then cooling to room temperature to obtain an aqueous suspension;

[0120] Step 2: The aqueous suspension obtained in step 1 is heated to 90° C., kept warm for 1 hour, and then a bead distribution regulator is added. After keeping warm for 5.3 hours, a mixed suspension material is obtained;

[0121] Step 3: Add a stabilizer to the mixed suspension material obtained in step 2 until the mixed suspension material is stable, fill the reactor with nitrogen, add a foaming agent, continue to heat to 122.5° C., keep warm at a pressure of 0.85 MPa for 2.2 hours, and then cool to 35° C. to obtain a bead material;

[0122] Step 4: Dehydrate and dry the bead material obtained in step 3, put it into a mixer, add an additive, stir for 10 minutes and then package to obtain a high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material.

[0123] The present invention has no particular limitation on the stabilizer, and various stabilizers known to those skilled in the art may be used, such as suspending agent TCP. The stable state of the mixed suspended material means that no particles in the suspended material sink.

[0124] The high-efficiency flame-retardant heat-insulating expandable polystyrene and graphite composite material of the present invention is a high-efficiency flame-retardant heat-insulating expandable polystyrene and graphite composite bead material, which is subsequently used to prepare corresponding materials according to actual needs, such as polystyrene (EPS) foam insulation board.

[0125] The present invention is specifically described below by way of examples. In addition, unless otherwise specified, all raw materials used are commercially available.

[0126] Example

[0127] Example 1

[0128] Embodiment 1 of the present invention provides a high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, comprising the following raw materials in parts by weight: 95 parts of styrene, 160 parts of desalted water, 6.3 parts of foaming agent, 0.3 parts of initiator, 0.2 parts of nucleating agent, 2.0 parts of flame retardant, 0.03 parts of inorganic sodium salt, 0.01 parts of graphite, 0.1 parts of inorganic suspending agent, 0.0002 parts of organic suspending agent, 0.002 parts of dispersant, 0.05 parts of inorganic additive, 0.002 parts of pH regulator, and 0.004 parts of bead distribution regulator.

[0129] The conductivity of the desalted water is 1μs / cm. The foaming agent is a mixture of isopentane and n-pentane, and the weight ratio of the two is 1:2.3. The initiator is a mixture of benzoyl peroxide, tert-butyl perbenzoate, tert-amyl peroxide-2-ethylhexyl carbonate, and diisopropylbenzene peroxide, and the weight ratio of the four is 6:1.5:1.5:3.25. The nucleating agent is polyethylene wax, purchased from Qingdao Haihao Chemical Co., Ltd., model H100P, molecular weight of 2000-2500 (average molecular weight of 2250). The flame retardant is decabromodiphenyl ethane. The inorganic sodium salt is tetrasodium phosphate. The dispersant is polyvinyl alcohol with a degree of alcoholysis of 88 mole%, which is PVA-217 of Kuraray of Japan. The inorganic additive is white carbon black, which is German Wacker white carbon black N20. The pH regulator is sodium bicarbonate. The organic suspending agent is hydroxyethyl cellulose; and the bead distribution regulator is sodium bisulfite.

[0130] The particle size of the graphite is 25 μm, and the graphite is surface-treated. The preparation method of the surface-treated graphite comprises the following steps: adding 0.79 parts by weight of graphite and 0.77 parts by weight of sodium lignin sulfonate to 55 parts by weight of pure water, heating to 70° C., stirring for 12 hours, washing with water, and drying to obtain the graphite.

[0131] The inorganic suspending agent is surface-treated active calcium phosphate, and its preparation method comprises the following steps: adding active calcium phosphate, lauric acid monoglyceride and water into a container according to the weight ratio of 1:0.08:55, stirring at 60°C until the active calcium phosphate is evenly mixed, and drying to obtain the surface-treated active calcium phosphate.

[0132] This embodiment also provides a method for preparing the high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, comprising the following steps:

[0133] Step 1: maintaining a rotation speed of 60 r / min, adding inorganic suspending agent, organic suspending agent, inorganic sodium salt, graphite, inorganic additives and stirring for 30 minutes, then adding styrene, nucleating agent, flame retardant, pH adjuster, initiator and stirring for 30 minutes, adding desalted water and dispersant into the reactor, stirring at 90°C for 30 minutes and then cooling to room temperature to obtain an aqueous suspension;

[0134] Step 2: The aqueous suspension obtained in step 1 is heated to 90° C., kept warm for 1 hour, and then a bead distribution regulator is added. After keeping warm for 5.3 hours, a mixed suspension material is obtained;

[0135] Step 3: Add a stabilizer to the mixed suspension material obtained in step 2 until the mixed suspension material is stable, fill the reactor with nitrogen, add a foaming agent, continue to heat to 122.5° C., keep warm at a pressure of 0.85 MPa for 2.2 hours, and then cool to 35° C. to obtain a bead material;

[0136] Step 4: Dehydrate, dry and package the bead material obtained in step 3 to obtain a highly efficient flame retardant and heat insulating expandable polystyrene and graphite composite material.

[0137] Example 2

[0138] Embodiment 2 of the present invention provides a high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, comprising the following raw materials in parts by weight: 70 parts of styrene, 150 parts of desalted water, 5 parts of foaming agent, 0.2 parts of initiator, 0.1 parts of nucleating agent, 0.5 parts of flame retardant, 0.01 parts of inorganic sodium salt, 0.01 parts of graphite, 0.05 parts of inorganic suspending agent, 0.0001 parts of organic suspending agent, 0.001 parts of dispersant, 0.01 parts of inorganic additive, 0.001 parts of pH adjuster, and 0.003 parts of bead distribution regulator.

[0139] The conductivity of the desalted water is 1 μs / cm. The foaming agent is a mixture of isopentane and n-pentane, and the weight ratio of the two is 1:2. The initiator is a mixture of benzoyl peroxide, tert-butyl perbenzoate, tert-amyl peroxide-2-ethylhexyl carbonate, and diisopropylbenzene peroxide, and the weight ratio of the four is 5:1:1:2.5. The nucleating agent is polyethylene wax, purchased from Qingdao Haihao Chemical Co., Ltd., model H100P, and the molecular weight is 2000-2500 (average molecular weight is 2250). The flame retardant is decabromodiphenylethane. The inorganic sodium salt is tetrasodium phosphate. The dispersant is polyvinyl alcohol with an alcoholysis degree of 88 mole%, which is PVA-217 of Kuraray of Japan. The inorganic additive is white carbon black, which is German Wacker white carbon black N20. The pH regulator is sodium bicarbonate. The organic suspending agent is hydroxyethyl cellulose; the bead distribution regulator is sodium bisulfite.

[0140] The particle size of the graphite is 20 μm, and the graphite is surface-treated. The preparation method of the surface-treated graphite comprises the following steps: adding 0.65 parts by weight of graphite and 0.65 parts by weight of sodium lignin sulfonate to 50 parts by weight of pure water, heating to 65° C., stirring for 10 hours, washing with water, and drying to obtain the graphite.

[0141] The inorganic suspending agent is surface-treated active calcium phosphate, and its preparation method comprises the following steps: adding active calcium phosphate, lauric acid monoglyceride and water into a container according to the weight ratio of 1:0.05:50, stirring at 50°C until the active calcium phosphate is evenly mixed, and drying to obtain the surface-treated active calcium phosphate.

[0142] This embodiment also provides a method for preparing the high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, comprising the following steps:

[0143] Step 1: maintaining a rotation speed of 50 r / min, adding inorganic suspending agent, organic suspending agent, inorganic sodium salt, and graphite, stirring for 20 minutes, then adding styrene, polyethylene wax, and initiator, stirring for 20 minutes, adding desalted water and dispersant into the reactor, stirring at 90°C for 20 minutes, and then cooling to room temperature to obtain an aqueous suspension;

[0144] Step 2: The aqueous suspension obtained in step 1 is heated to 85°C, kept warm for 0.5 hours, and then a bead distribution regulator is added. After keeping warm for 5 hours, a mixed suspension material is obtained;

[0145] Step 3: Add the suspending agent TCP to the mixed suspension material obtained in step 2 until the mixed suspension material is stable, fill the reactor with nitrogen, add the foaming agent, continue to heat to 115°C, keep warm at 0.8MPa pressure for 2h, and then cool to 30°C to obtain a bead material;

[0146] Step 4: Dehydrate, dry and package the bead material obtained in step 3 to obtain a highly efficient flame retardant and heat insulating expandable polystyrene and graphite composite material.

[0147] Example 3

[0148] Embodiment 3 of the present invention provides a high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, comprising the following raw materials in parts by weight: 100 parts of styrene, 240 parts of desalted water, 7.6 parts of foaming agent, 0.7 parts of initiator, 0.5 parts of nucleating agent, 4.5 parts of flame retardant, 0.08 parts of inorganic sodium salt, 3 parts of graphite, 0.2 parts of inorganic suspending agent, 0.0005 parts of organic suspending agent, 0.005 parts of dispersant, 2 parts of inorganic additive, 0.005 parts of pH regulator, and 0.005 parts of bead distribution regulator.

[0149] The conductivity of the desalted water is 1 μs / cm. The foaming agent is a mixture of isopentane and n-pentane, and the weight ratio of the two is 1:3. The initiator is a mixture of benzoyl peroxide, tert-butyl perbenzoate, tert-amyl peroxide-2-ethylhexyl carbonate, and diisopropylbenzene peroxide, and the weight ratio of the four is 7:2:2:4. The nucleating agent is polyethylene wax, purchased from Qingdao Haihao Chemical Co., Ltd., model H100P, and the molecular weight is 2000-2500 (average molecular weight is 2250). The flame retardant is decabromodiphenylethane. The inorganic sodium salt is tetrasodium phosphate. The dispersant is polyvinyl alcohol with a degree of alcoholysis of 88 mole%, which is PVA-217 from Kuraray of Japan. The inorganic additive is white carbon black, which is German Wacker white carbon black N20. The pH regulator is sodium bicarbonate. The organic suspending agent is hydroxyethyl cellulose; the bead distribution regulator is sodium bisulfite.

[0150] The particle size of the graphite is 30 μm, and the graphite is surface-treated. The preparation method of the surface-treated graphite comprises the following steps: adding 0.93 parts by weight of graphite and 0.9 parts by weight of sodium lignin sulfonate to 60 parts by weight of pure water, heating to 75° C., stirring for 14 hours, washing with water, and drying to obtain the graphite.

[0151] The inorganic suspending agent is surface-treated active calcium phosphate, and its preparation method comprises the following steps: adding active calcium phosphate, lauric acid monoglyceride and water into a container according to the weight ratio of 1:0.12:60, stirring at 70°C until the active calcium phosphate is evenly mixed, and drying to obtain the surface-treated active calcium phosphate.

[0152] This embodiment also provides a method for preparing the high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, comprising the following steps:

[0153] Step 1: maintaining a rotation speed of 70 r / min, adding inorganic suspending agent, organic suspending agent, inorganic sodium salt, and graphite, stirring for 40 minutes, then continuing to add styrene, polyethylene wax, and initiator, stirring for 40 minutes, adding desalted water and dispersant into the reactor, stirring at 90°C for 40 minutes, and then cooling to room temperature to obtain an aqueous suspension;

[0154] Step 2: The aqueous suspension obtained in step 1 is heated to 90° C., kept warm for 1.5 hours, and then a bead distribution regulator is added. After keeping warm for 6 hours, a mixed suspension material is obtained;

[0155] Step 3: Add the suspending agent TCP to the mixed suspension material obtained in step 2 until the mixed suspension material is stable, fill the reactor with nitrogen, add the foaming agent, continue to heat to 130° C., keep warm at a pressure of 0.8-0.9 MPa for 2.5 hours, and then cool to 40° C. to obtain a bead material;

[0156] Step 4: Dehydrate, dry and package the bead material obtained in step 3 to obtain a highly efficient flame retardant and heat insulating expandable polystyrene and graphite composite material.

[0157] Example 4

[0158] Example 4 of the present invention provides a high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, and its specific implementation is similar to that of Example 1, except that the particle size of the graphite is replaced from 25 μm to 1 μm.

[0159] Example 5

[0160] Example 5 of the present invention provides a high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, and its specific implementation is similar to that of Example 1, except that the particle size of the graphite is replaced from 25 μm to 50 μm.

[0161] Example 6

[0162] Example 6 of the present invention provides a high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, and its specific implementation method is similar to that of Example 1, except that the sodium lignin sulfonate in the preparation method of the surface-treated graphite is replaced by sodium dodecylbenzene sulfonate (CAS No. 25155-30-0).

[0163] Example 7

[0164] Example 7 of the present invention provides a high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, and its specific implementation is similar to that of Example 1, except that the particle size of the graphite is replaced from 25 μm to 0.5 μm.

[0165] Example 8

[0166] Example 8 of the present invention provides a high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, and its specific implementation is similar to that of Example 1, except that the particle size of the graphite is replaced from 25 μm to 55 μm.

[0167] Example 9

[0168] Example 9 of the present invention provides a high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, and its specific implementation method is similar to that of Example 1, except that the sodium lignin sulfonate in the preparation method of the surface-treated graphite is replaced by sodium dodecyl sulfonate (CAS No. 2386-53-0).

[0169] Example 10

[0170] Example 10 of the present invention provides a high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, and its specific implementation method is similar to that of Example 1, except that the weight portion of sodium lignin sulfonate in the preparation method of the surface-treated graphite is replaced from 0.77 parts to 0 parts.

[0171] Embodiment 11

[0172] Example 11 of the present invention provides a high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, and its specific implementation is similar to that of Example 1, except that the weight portion of the graphite is replaced from 2.75 parts to 0 parts.

[0173] Example 12

[0174] Example 12 of the present invention provides a high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, and its specific implementation method is similar to that of Example 1, except that the monolaurin in the preparation method of the surface-treated active calcium phosphate is replaced by sodium dodecyl sulfate (CAS No. 2386-53-0).

[0175] Embodiment 13

[0176] Example 13 of the present invention provides a high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, and its specific implementation method is similar to that of Example 1, except that monolaurin is not added in the preparation method of the surface-treated active calcium phosphate.

[0177] Embodiment 14

[0178] Example 14 of the present invention provides a high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, and its specific implementation method is similar to that of Example 1, except that the weight portion of the inorganic suspending agent active calcium phosphate is replaced from 0.25 parts to 0 parts.

[0179] Embodiment 15

[0180] Example 15 of the present invention provides a high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, and its specific implementation is similar to that of Example 1, except that the weight portion of the inorganic suspending agent active calcium phosphate is 0.01 parts.

[0181] Example 16

[0182] Example 16 of the present invention provides a high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, and its specific implementation method is similar to that of Example 1, except that the weight portion of the inorganic suspending agent active calcium phosphate is replaced from 0.25 parts to 0.25 parts.

[0183] Embodiment 17

[0184] Example 17 of the present invention provides a high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, and its specific implementation is similar to that of Example 1, except that the weight portion of the organic suspending agent hydroxyethyl cellulose is replaced from 0.1 parts to 0 parts.

[0185] Embodiment 18

[0186] Example 18 of the present invention provides a high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, and its specific implementation is similar to that of Example 1, except that the weight portion of the organic suspending agent hydroxyethyl cellulose is replaced from 0.1 part to 0.001 part.

[0187] Embodiment 19

[0188] Example 19 of the present invention provides a high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, and its specific implementation method is similar to that of Example 1, except that the dispersant is replaced by polyvinyl alcohol with a degree of alcoholysis of 88 mole% with polyvinyl alcohol with a degree of alcoholysis of 98.5 mole%, which is PVA-105 of Kuraray of Japan, and the degree of alcoholysis is 98-99 mole% (the average value is 98.5 mole%).

[0189] Embodiment 20

[0190] Embodiment 20 of the present invention provides a high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, comprising the following raw materials in parts by weight: 95 parts of styrene, 160 parts of desalted water, 6.3 parts of foaming agent, 0.3 parts of initiator, 0.2 parts of nucleating agent, 2.0 parts of flame retardant, 0.03 parts of inorganic sodium salt, 0.01 parts of graphite, 0.1 parts of inorganic suspending agent, 0.0002 parts of organic suspending agent, 0.002 parts of dispersant, 0.05 parts of inorganic additive, 0.002 parts of pH adjusting agent, 0.004 parts of bead distribution adjusting agent, 0.29 parts of zinc stearate, 0.225 parts of monoglyceride, and 0.015 parts of polyethylene glycol (PEG-400).

[0191] The conductivity of the desalted water is 1μs / cm. The foaming agent is a mixture of isopentane and n-pentane, and the weight ratio of the two is 1:2.3. The initiator is a mixture of benzoyl peroxide, tert-butyl perbenzoate, tert-amyl peroxide-2-ethylhexyl carbonate, and diisopropylbenzene peroxide, and the weight ratio of the four is 6:1.5:1.5:3.25. The nucleating agent is polyethylene wax, purchased from Qingdao Haihao Chemical Co., Ltd., model H100P, molecular weight of 2000-2500 (average molecular weight of 2250). The flame retardant is decabromodiphenyl ethane. The inorganic sodium salt is tetrasodium phosphate. The dispersant is polyvinyl alcohol with a degree of alcoholysis of 88 mole%, which is PVA-217 of Kuraray of Japan. The inorganic additive is white carbon black, which is German Wacker white carbon black N20. The pH regulator is sodium bicarbonate. The organic suspending agent is hydroxyethyl cellulose; and the bead distribution regulator is sodium bisulfite.

[0192] The particle size of the graphite is 25 μm, and the graphite is surface-treated. The preparation method of the surface-treated graphite comprises the following steps: adding 0.79 parts by weight of graphite and 0.77 parts by weight of sodium lignin sulfonate to 55 parts by weight of pure water, heating to 70° C., stirring for 12 hours, washing with water, and drying to obtain the graphite.

[0193] The inorganic suspending agent is surface-treated active calcium phosphate, and its preparation method comprises the following steps: adding active calcium phosphate, lauric acid monoglyceride and water into a container according to the weight ratio of 1:0.08:55, stirring at 60°C until the active calcium phosphate is evenly mixed, and drying to obtain the surface-treated active calcium phosphate.

[0194] This embodiment also provides a method for preparing the high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, comprising the following steps:

[0195] Step 1: maintaining a rotation speed of 60 r / min, adding inorganic suspending agent, organic suspending agent, inorganic sodium salt, graphite, inorganic additives and stirring for 30 minutes, then adding styrene, nucleating agent, flame retardant, pH adjuster, initiator and stirring for 30 minutes, adding desalted water and dispersant into the reactor, stirring at 90°C for 30 minutes and then cooling to room temperature to obtain an aqueous suspension;

[0196] Step 2: The aqueous suspension obtained in step 1 is heated to 90° C., kept warm for 1 hour, and then a bead distribution regulator is added. After keeping warm for 5.3 hours, a mixed suspension material is obtained;

[0197] Step 3: Add a stabilizer to the mixed suspension material obtained in step 2 until the mixed suspension material is stable, fill the reactor with nitrogen, add a foaming agent, continue to heat to 122.5° C., keep warm at a pressure of 0.85 MPa for 2.2 hours, and then cool to 35° C. to obtain a bead material;

[0198] Step 4: Dehydrate, dry and package the bead material obtained in step 3 to obtain a highly efficient flame retardant and heat insulating expandable polystyrene and graphite composite material.

[0199] Embodiment 21

[0200] Example 21 of the present invention provides a high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, and its specific implementation method is similar to that of Example 1, except that the weight part of the zinc stearate is replaced from 0.29 part to 0.25 part, the weight part of monoglyceride is replaced from 0.225 part to 0.15 part, and the weight part of polyethylene glycol (PEG-400) is replaced from 0.015 part to 0.01 part.

[0201] Embodiment 22

[0202] Example 22 of the present invention provides a high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material, and its specific implementation method is similar to that of Example 1, except that the weight part of zinc stearate is replaced by 0.29 part to 0.33 part, the weight part of monoglyceride is replaced by 0.225 part to 0.30 part, and the weight part of polyethylene glycol (PEG-400) is replaced by 0.015 part to 0.02 part.

[0203] Performance Evaluation

[0204] 1. Bead material content test: After the high-efficiency flame-retardant and heat-insulating expandable polystyrene obtained in Examples 1 to 22 is uniformly mixed with the graphite composite material, 10 positions are randomly selected to obtain samples until the samples just cover the entire bottom of the culture dish (size 60 mm), and the bead material content in the sample is evaluated. If the bead material content is ≥90%, it is recorded as 0; if the bead material content is <90%, it is recorded as ×.

[0205] 2. Flame retardant properties:

[0206] ① Critical thermal radiation flux test: The high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite materials obtained in Examples 1 to 22 were prepared into polystyrene board samples with dimensions of 1050 mm in length × 230 mm in width × 60 mm in thickness by a method well known to those skilled in the art in accordance with GB / T 11785-2005 “Radiation Heat Source Method for Combustion Performance of Paving Materials”. The radiation flux (CHF) at the point where the flame is extinguished or the radiation flux corresponding to the farthest position to which the flame propagates during the test for 30 minutes (HF-30) was obtained by testing, and the lowest value of the two was selected as the critical thermal radiation flux.

[0207] ② Test of flame tip height Fs within 20 seconds: The high-efficiency flame retardant and heat-insulating expandable polystyrene and graphite composite materials obtained in Examples 1 to 22 are prepared into polystyrene board samples with dimensions of 250 mm in length × 90 mm in width × 60 mm in thickness by a method well known to those skilled in the art in accordance with GB / T 8626 “Test method for flammability of building materials”. The flame tip height Fs is tested at 20 seconds using a surface ignition method in a combustion box at an air flow rate of 0.7 m / s.

[0208] ③ Combustion performance classification: Based on the above test data, the combustion performance of the samples is classified according to GB8624-2012 "Combustion performance classification of building materials and products". Among them, Class B means the critical thermal radiation flux is ≥8.0kW / m 2 , flame tip height Fs≤150mm within 20s; C level: critical thermal radiation flux ≥4.5kW / m 2 , flame tip height Fs≤150mm within 20s; Class D is critical thermal radiation flux ≥3.0kW / m 2 , flame tip height Fs≤150mm within 20s; Class E: critical thermal radiation flux ≥2.2kW / m 2 , the flame tip height Fs within 20s is ≤150mm; if the above requirements are not met, it is recorded as F. The results are shown in Table 1.

[0209] 3. Thermal conductivity test: The high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite materials obtained in Examples 1 to 16 and Examples 20 to 21 were prepared into polystyrene plate samples with a size of 250 mm long × 90 mm wide × 60 mm thick by a method well known to those skilled in the art in accordance with GB / T10294-2008 "Measurement of Steady-State Thermal Resistance and Related Properties of Insulating Materials - Guarded Hot Plate Method", and the thermal conductivity value was measured by a thermal conductivity measuring instrument. After three tests, the average value was calculated, and the results are shown in Table 1.

[0210] 4. Mechanical properties test: The high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite materials obtained in Examples 1 to 22 were made into dumbbell shapes using a method well known to those skilled in the art in accordance with GB9641-1988 "Test method for tensile properties of rigid foam plastics", and the tensile properties were tested using a testing machine at 25°C. The results are shown in Table 1.

[0211] Table 1 Performance test results

[0212]

[0213]

[0214] Based on the above experimental results, it can be seen that the present invention uses styrene, graphite, inorganic suspending agent, organic suspending agent and other additives to prepare a highly efficient flame retardant and heat insulating expandable polystyrene and graphite composite material with excellent performance. The content test of the bead material shows that the content of the bead material is ≥90%, and the powder particles are less; the flame retardant performance test shows that its combustion performance completely reaches Class B, and has good flame retardant and fireproof performance; the thermal conductivity test shows that the thermal conductivity is 0.026~0.032W / (m·K), and has excellent thermal insulation performance; the mechanical performance test shows that the tensile strength is 0.15~0.35MPa, and the mechanical properties are excellent while ensuring flame retardant and heat insulation performance.

[0215] The foregoing examples are merely illustrative and are used to explain some features of the method of the present invention. The appended claims are intended to claim the widest possible range that can be conceived, and the embodiments presented herein are only illustrations of selected implementations according to the combination of all possible embodiments. Therefore, the applicant intends that the appended claims are not limited by the selection of examples that illustrate the features of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention.

Claims

1. A highly efficient flame retardant and heat insulating expandable polystyrene and graphite composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 95 parts of styrene, 160 parts of desalted water, 6.3 parts of foaming agent, 0.3 parts of initiator, 0.2 parts of nucleating agent, 2.0 parts of flame retardant, 0.03 parts of inorganic sodium salt, 0.01 parts of graphite, 0.1 parts of inorganic suspending agent, 0.0002 parts of organic suspending agent, 0.002 parts of dispersant, 0.05 parts of inorganic filler, 0.002 parts of pH regulator, 0.004 parts of bead distribution regulator, 0.29 parts of zinc stearate, 0.225 parts of monoglyceride and 0.015 parts of polyethylene glycol PEG-400; The conductivity of the desalted water is 1 μs / cm; The foaming agent is a mixture of isopentane and normal pentane, and the weight ratio of the two is 1:2.3; The initiator is a mixture of benzoyl peroxide, tert-butyl perbenzoate, tert-amyl peroxide-2-ethylhexyl carbonate, and diisopropylbenzene peroxide, and the weight ratio of the four is 6:1.5:1.5:3.25; the nucleating agent is polyethylene wax purchased from Qingdao Haihao Chemical Co., Ltd., model H100P, molecular weight of 2000-2500, and average molecular weight of 2250; The flame retardant is decabromodiphenylethane; the inorganic sodium salt is tetrasodium phosphate; the dispersant is polyvinyl alcohol with an alcoholysis degree of 88 mole%, which is PVA-217 from Kuraray of Japan; the inorganic additive is white carbon black, which is white carbon black N20 from Wacker of Germany; the pH regulator is sodium bicarbonate; the organic suspending agent is hydroxyethyl cellulose; and the bead distribution regulator is sodium bisulfite; The graphite has a particle size of 25 μm and is surface-treated graphite. The preparation method of the surface-treated graphite comprises the following steps: adding 0.79 parts by weight of graphite and 0.77 parts by weight of sodium lignin sulfonate to 55 parts by weight of pure water, heating to 70° C., stirring for 12 hours, washing with water, and drying to obtain the graphite. The inorganic suspending agent is a surface-treated active calcium phosphate, and the preparation method thereof comprises the following steps: adding active calcium phosphate, lauric acid monoglyceride and water in a weight ratio of 1:0.08:55 into a container, stirring at 60° C. until the active calcium phosphate is uniformly mixed, and drying to obtain the surface-treated active calcium phosphate; The method for preparing the high-efficiency flame-retardant and heat-insulating expandable polystyrene and graphite composite material comprises the following steps: Step 1: maintaining a rotation speed of 60 r / min, adding inorganic suspending agent, organic suspending agent, inorganic sodium salt, graphite, inorganic additives and stirring for 30 minutes, then adding styrene, nucleating agent, flame retardant, pH adjuster, initiator and stirring for 30 minutes, adding desalted water and dispersant into the reactor, stirring at 90°C for 30 minutes and then cooling to room temperature to obtain an aqueous suspension; Step 2: The aqueous suspension obtained in step 1 is heated to 90° C., kept warm for 1 hour, and then a bead distribution regulator is added. After keeping warm for 5.3 hours, a mixed suspension material is obtained; Step 3: Add a stabilizer to the mixed suspension material obtained in step 2 until the mixed suspension material is stable, fill the reactor with nitrogen, add a foaming agent, continue to heat to 122.5° C., keep warm at a pressure of 0.85 MPa for 2.2 hours, and then cool to 35° C. to obtain a bead material; Step 4: Dehydrate, dry and package the bead material obtained in step 3 to obtain a highly efficient flame retardant and heat insulating expandable polystyrene and graphite composite material.

Citation Information

Patent Citations

  • High flame retardancy low heat conduction graphite expandable polystyrene product and production method of same

    CN106117398A